Penerimaan terhadap Anggota Keluarga yang Pindah Agama - Anggy Wirnasary (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2021)
This study aims to determine the family's motives for changing attitudes from refusing to accepting back their family members who converted to Islam (converts). This study was a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and relevant literature. This study found that families changed from refusing became accept their family members who converted to Muslims driven by several things: (1) psychological-emotional motivation in the form of affection for children; (2) Economic pragmatic reasons because children who convert to Islam are able to meet the economic needs of the family, and; (3) The ability of converts to take the